2015
DOI: 10.1371/journal.pone.0140717
|View full text |Cite
|
Sign up to set email alerts
|

Panitumumab Use in Metastatic Colorectal Cancer and Patterns of KRAS Testing: Results from a Europe-Wide Physician Survey and Medical Records Review

Abstract: BackgroundFrom 2008–2013, the European indication for panitumumab required that patients’ tumor KRAS exon 2 mutation status was known prior to starting treatment. To evaluate physician awareness of panitumumab prescribing information and how physicians prescribe panitumumab in patients with metastatic colorectal cancer (mCRC), two European multi-country, cross-sectional, observational studies were initiated in 2012: a physician survey and a medical records review. The first two out of three planned rounds for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…However, in a recent study of patients with mCRC evaluated for first‐line therapy, ~25% of patients did not have RAS testing requested at or at least one month after their initial diagnosis of metastatic disease (Longin, ). These findings are supported by a survey of European physicians, which revealed that RAS testing turnaround times and the unavailability of tissue were the most frequent factors cited for treating mCRC patients with unknown KRAS status (Trojan et al ., ). Moreover, a recent EQA survey found that half of all participating laboratories exceeded the required turnaround time of 14 days for RAS testing (Tack et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, in a recent study of patients with mCRC evaluated for first‐line therapy, ~25% of patients did not have RAS testing requested at or at least one month after their initial diagnosis of metastatic disease (Longin, ). These findings are supported by a survey of European physicians, which revealed that RAS testing turnaround times and the unavailability of tissue were the most frequent factors cited for treating mCRC patients with unknown KRAS status (Trojan et al ., ). Moreover, a recent EQA survey found that half of all participating laboratories exceeded the required turnaround time of 14 days for RAS testing (Tack et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The detailed methodology of Rounds 1 and 2 (assessing KRAS only) for both the physician survey and MRR, conducted from 2012 to 2013, has been published in full previously [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two studies – a physician survey and a medical records review (MRR) – were initiated in Europe in 2012 to evaluate physicians’ awareness of the correct therapeutic indication for panitumumab and to establish if it was being prescribed in accordance with this indication, which is to patients with mCRC and confirmed wild-type KRAS tumour status prior to treatment with panitumumab. The studies were carried out in three consecutive rounds; the results of the first two rounds of both studies have been published previously [ 18 ]. Overall in Rounds 1 and 2 of the physician survey, 298 (99.0%) of 301 physicians responded correctly that panitumumab should be administered only to patients with confirmed KRAS wild-type tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the 2009 ASCO guidelines, recent literature has shown increased physician awareness of the need for KRAS testing and increased testing rates [15] . However, 50% or more of eligible patients do not receive the test [ 6 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%